Controlling institutions : international organizations and the global economy - Stone, Randall W. , 1966- (Cambridge : Cambridge University Press, 2011)
Argues that informal state power explains the institutional design, performance shortcomings and legitimacy problems in international organizations
1. Introduction: international organization and US power -- 2. A theory of international organization -- 3. A model of informal governance -- 4. Informal governance in the IMF -- 5. The World Trade Organization -- 6. The European Union -- 7. Access to IMF resources -- 8. Conditionality under IMF programs -- 9. Enforcement -- 10. Conclusions
Includes bibliographical references (p. [240]-250) and index
Keywords: International agencies -- Rules and practice; International agencies -- Management; International organization